Immediate Removal From Activity After Sport-Related Concussion Is Associated With Shorter Clinical Recovery and Less Severe Symptoms in Collegiate Student-Athletes. Issue 6 (May 2018) - Asken, Breton M.; Bauer, Russell M.; Guskiewicz, Kevin M.; McCrea, Michael A.; Schmidt, Julianne D.; Giza, Christopher C.; Snyder, Aliyah R.; Houck, Zachary M.; Kontos, Anthony P.; McAllister, Thomas W.; Broglio, Steven P.; Clugston, James R.; et al.
Background: Timely removal from activity after concussion symptoms remains problematic despite heightened awareness. Previous studies indicated potential adverse effects of continuing to participate in physical activity immediately after sustaining a concussion. Hypothesis/Purpose: The purpose was to determine the effect of timing of removal from play after concussion on clinical outcomes. It was hypothesized that immediate removal from activity after sport-related concussion (SRC) would be associated with less time missed from sport, a shorter symptomatic period, and better outcomes on acute clinical measures. Study Design: Cohort study; Level of evidence, 3. Methods: Data were reported from the National Collegiate Athletic Association and Department of Defense Grand Alliance: Concussion Awareness, Research, and Education (CARE) Consortium. Participants with 506 diagnosed SRCs from 18 sports and 25 institutions and military service academies were analyzed and classified as either immediate removal from activity (I-RFA) or delayed removal from activity (D-RFA). Outcomes of interest included time missed from sport attributed to their SRC, symptom duration, and clinical assessment scores. Results: There were 322 participants (63.6%) characterized as D-RFA. I-RFA status was associated with significantly less time missed from sport ( R 2 change = .022-.024, P < .001 to P = .001) and shorter symptom duration ( R 2 change = .044-.046, P < .001 [all imputations]) while controlling for other SRC recovery modifiers. These athletes missed approximately 3 fewer days from sport participation. I-RFA athletes had significantly less severe acute SRC symptoms and were at lower risk of recovery taking ≥14 days (relative risk = .614, P < .001, small-medium effect size) and ≥21 days (relative risk = .534, P = .010, small effect size). Conclusion: I-RFA is a protective factor associated with less severe acute symptoms and shorter recovery after SRC. Conveying this message to athletes, coaches, and others involved in the care of athletes may promote timely injury reporting.